Detection of Mycovirus in Sclerotium Rolfsii, A Phytopathogenic Fungus in Bangladesh (Bangladesh Journal of Agricultural Research, 2023)
A research project was conducted to detect presence of mycovirus, a probable virocontrol agent in Sclerotium rolfsii, a destructive soil-borne plant pathogenic fungus. A total of 500 isolates of the pathogen was isolated from infected wheat, bush bean, tomato, eggplant, lentil, chickpea, eggplant, chilli and okra grown Bangladesh following tissue planting methods and brought to the Virology laboratory of Okayama University, Japan. After brought to Japan, a total of 472 isolates were re-isolated and the fungal isolates were cultured on potato dextrose agar for extraction of DNA and dsRNA. The extracted nucleic acids were tested for the presence of viruses using rolling circle amplification (RCA) (for DNA viruses) and cellulose column chromatography (for RNA viruses). The detected S. rolfsii viruses were further characterized molecularly. For detection of DNA virus, a total of 120 isolates were tested, none were found positive for DNA viruses. For detection of dsRNA virus, a total of 472 isolates were tested, 7 isolates showed possible dsRNA positive band. The partial cDNA sequences of the dsRNA segments isolated from the strain SR336 were obtained. BlastX database search with the partial sequence from SR336 isolates showed similarities with randorna like virus. To screen the presence of randorna like virus in S. rolfsii isolates, 64 isolates were selected from 472 isolates of S. rolfsii. The isolates of S. rolfsii were tested by RT-PCR using randorna virus specific primers. Out of 64 isolates 13, (20.31%) isolates were randorna virus positive strain and rest of the isolates were absent of randorna virus.Bangladesh J. Agril. Res. 46(3): 331-341, September 2021